Repair of composite restorations – Teaching information from dental schools of the State of Rio Grande do Sul (RS), Brazil (Revista da Faculdade de Odontologia - UPF, 2012)
Objective: The present study analyzed the teaching of repair of direct composite restorations (RCR) and its determining factors in Dental Schools of the State of Rio Grande do Sul (RS), Brazil. Methods: Eight Schools were selected based on registration on the website of the Ministry of Education (MEC). A first contact was made by phone, and the e-mail of the head of the Restorative Department was obtained. A questionnaire was elaborated containing 19 questions, and was e-mailed to the dental schools. Data was analyzed by descriptive statistics. Results: Six from the eight schools selected returned the questionnaire. All participating schools fulfill and teach RCR and consider the technique successful as treatment. The schools did not present any reason for not accomplishing it. The main indications for repair were shade correction, fracture of the material and fracture of the tooth. In most schools the nature of the teaching is theoretical, in clinical disciplines. Conclusions: A consistent conduct towards teaching RCR was observed from 100% of the participating schools. Most of them consider it a definitive treatment, revealing a trend towards the preservation of tooth structure.